Immune Checkpoint Molecule TIGIT Regulates Kidney T Cell Functions and Contributes to AKI. Issue 5 (13th May 2023) - Noel, Sanjeev; Lee, Kyungho; Gharaie, Sepideh; Kurzhagen, Johanna T.; Pierorazio, Philip M.; Arend, Lois J.; Kuchroo, Vijay K.; Cahan, Patrick; Rabb, Hamid
Abstract : Abstract : Significance Statement: T cells mediate pathogenic and reparative processes during AKI, but the exact mechanisms regulating kidney T cell functions are unclear. This study identified upregulation of the novel immune checkpoint molecule, TIGIT, on mouse and human kidney T cells after AKI. TIGIT-expressing kidney T cells produced proinflammatory cytokines and had effector (EM) and central memory (CM) phenotypes. TIGIT-deficient mice had protection from both ischemic and nephrotoxic AKI. Single-cell RNA sequencing led to the discovery of possible downstream targets of TIGIT. TIGIT mediates AKI pathophysiology, is a promising novel target for AKI therapy, and is being increasingly studied in human cancer therapy trials. Background: T cells play pathogenic and reparative roles during AKI. However, mechanisms regulating T cell responses are relatively unknown. We investigated the roles of the novel immune checkpoint molecule T cell immunoreceptor with Ig and immunoreceptor tyrosine-based inhibitory motif domains (TIGIT) in kidney T cells and AKI outcomes. Methods: TIGIT expression and functional effects were evaluated in mouse kidney T cells using RNA sequencing (RNA-Seq) and flow cytometry. TIGIT effect on AKI outcomes was studied with TIGIT knockout (TIGIT-KO) mice in ischemia reperfusion (IR) and cisplatin AKI models. Human kidney T cells from nephrectomy samples and single cell RNA sequencing (scRNA-Seq) data from the Kidney Precision Medicine Project were used to assess TIGIT's role in humans. Results: RNA-Seq and flow cytometry analysis of mouse kidney CD4+ T cells revealed increased expression of TIGIT after IR injury. Ischemic injury also increased TIGIT expression in human kidney T cells, and TIGIT expression was restricted to T/natural killer cell subsets in patients with AKI. TIGIT-expressing kidney T cells in wild type (WT) mice had an effector/central memory phenotype and proinflammatory profile at baseline and post-IR. Kidney regulatory T cells were predominantly TIGIT+ and significantly reduced post-IR. TIGIT-KO mice had significantly reduced kidney injury after IR and nephrotoxic injury compared with WT mice. scRNA-Seq analysis showed enrichment of genes related to oxidative phosphorylation and mTORC1 signaling in Th17 cells from TIGIT-KO mice. Conclusions: TIGIT expression increases in mouse and human kidney T cells during AKI, worsens AKI outcomes, and is a novel therapeutic target for AKI.